The Power of Social Media: A Narrative Analysis of Rohingya Refugee Rejection on TikTok - Munirah; Jannah, Rauzatul; Amalia; Zamziba, Muhammad Nur Farhan (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2025)
This study explores how TikTok social media narratives affect public opinion on social issues related to Rohingya refugees in Aceh. This study analyzes the narrative of Rohingya refugee rejection in Aceh by studying TikTok social media content produced by Ali Hamzah, a content creator with 1.1 million followers. The focus of the research is the shift in the perspective of the Acehnese people from acceptance in 2015 to rejection in 2023-2024. This research uses a qualitative approach with a content analysis method to examine TikTok videos uploaded by Ali Hamzah from December 2023 to July 2024 with the theme of Rohingya refugees. The data were analyzed using thematic coding techniques to identify dominant narrative patterns. The results show that the narrative of rejection is formed through three main themes: criticism of the shelter system, security and legality issues, and socio-economic impact. Ali Hamzah uses a narrative strategy that includes emotional language, persuasive visual techniques, and framing the issue as a national security threat. The content produced by Ali Hamzah strengthens the shift in Acehnese’s perception of Rohingya refugees. This shift in perception has an impact on the refusal of Rohingya refugees by the Aceh people. The study concludes that social media plays an important role in shaping and reinforcing the sentiment of rejection towards Rohingya refugees in Aceh.